A New Antibiotic-Loaded Sol-Gel Can Prevent Bacterial Prosthetic Joint Infection: From in vitro Studies to an in vivo Model - Aguilera-Correa, John Jairo; Garcia-Casas, Amaya; Mediero, Aranzazu; Romera, David; Mulero, Francisca; Cuevas-López, Irene; Jiménez-Morales, Antonia; Esteban, Jaime (Frontiers in Microbiology, 2020)
The aim of this study was to evaluate the effect of a moxifloxacin-loaded organic-inorganic sol-gel with different antibiotic concentration in the in vitro biofilm development and treatment against Staphylococcus aureus, S. epidermidis, and Escherichia coli, cytotoxicity and cell proliferation of MC3T3-E1 osteoblasts; and its efficacy in preventing the prosthetic joint infection (PJI) caused by clinical strains of S. aureus and E. coli using an in vivo murine model. Three bacterial strains, S. epidermidis ATCC 35984, S. aureus 15981, and, E. coli ATCC 25922, were used for microbiological studies. Biofilm formation was induced using tryptic-soy supplemented with glucose for 24 h, and then, adhered and planktonic bacteria were estimated using drop plate method and absorbance, respectively. A 24-h-mature biofilm of each species growth in a 96-well plate was treated for 24 h using a MBECTM biofilm Incubator lid with pegs coated with the different types of sol-gel, after incubation, biofilm viability was estimated using alamrBlue. MC3T3-E1 cellular cytotoxicity and proliferation were evaluated using CytoTox 96 Non-Radioactive Cytotoxicity Assay and alamarBlue, respectively. The microbiological studies showed that sol-gel coatings inhibited the biofilm development and treated to a mature biofilm of three evaluated bacterial species. The cell studies showed that the sol-gel both with and without moxifloxacin were non-cytotoxic and that cell proliferation was inversely proportional to the antibiotic concentration containing by sol-gel. In the in vivo study, mice weight increased over time, except in the E. coli-infected group without coating. The most frequent symptoms associated with infection were limping and piloerection; these symptoms were more frequent in infected groups with non-coated implants than infected groups with coated implants. The response of moxifloxacin-loaded sol-gel to infection was either total or completely absent. No differences in bone mineral density were observed between groups with coated and non-coated implants and macrophage presence lightly increased in the bone grown directly in contact with the antibiotic-loaded sol-gel. In conclusion, moxifloxacin-loaded sol-gel coating is capable of preventing PJI caused by both Gram-positive and Gram-negative species.